2012
DOI: 10.4314/wsa.v35i3.76764
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology, sediment transport dynamics and geomorphology of a variable flow river: The Mfolozi River, South Africa

Abstract: The co-efficient of variation for inter-annual streamflow of the Mfolozi River is extremely high at 79%. An analysis of flow frequency indicated that streamflow is skewed towards low-flow values, with a number of extremely large flood events occurring as outliers on the histogram. Streamflow variability in the Mfolozi River may be linked to multiple factors including a large catchment size, a seasonal climate of a dry winter and wet summer, evergreen vegetation in the catchment, variable precipitation and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The dominant vegetation types in the floodplain system include Cyperus papyrus , Phragmites mauritianus , Phragmites australis and Ficus trichopoda . The uMfolozi River has a highly variable flow regime [ 36 ], characterized by a low base-flow and a few large but brief floods each year. Floods are a feature of the river and they have a profound influence on the geomorphology of the floodplain [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant vegetation types in the floodplain system include Cyperus papyrus , Phragmites mauritianus , Phragmites australis and Ficus trichopoda . The uMfolozi River has a highly variable flow regime [ 36 ], characterized by a low base-flow and a few large but brief floods each year. Floods are a feature of the river and they have a profound influence on the geomorphology of the floodplain [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The clearance of land for cultivation of sugarcane and commercial forestry dates back to 1911 [38]. By 1960, more than 50% of the floodplain had been converted to sugarcane farms whose establishment was made possible by the construction of canals, diversion of the uMfolozi River and the clearing of indigenous wetland vegetation [31,36]. The floodplain also supports subsistence farming of other crops wherein the dominant ones include sweet potato (Ipomoea batatas), banana (Musa acuminate), and amadumbe (Colocasia esculenta).…”
Section: Study Area Backgroundmentioning
confidence: 99%
“…A POC concentration of 2.57x10 10 g y -1 was calculated using the sediment concentration and the assumption that POC was 8.4% of TSS [59]. DOC imports were calculated based on an average global estimate of 6 mg L -1 [59], a January flow rate of 6x10 10 L and a June flow rate of 6x10 9 L for the Mfolozi River [61]. A summary of imports can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…has shown that this relationship is likely to vary on different timescales owing to changing sediment availability along drainage lines and variable sediment delivery from inter-drainage areas (e.g. Walling, 1977;Grenfell and Ellery, 2009). However, the different scenarios corresponding to values for the exponent b of 0.5, 1 and 1.5 represent a range of possible relationships that likely includes a scenario that can be considered realistic (Syvitski et al, 2000).…”
Section: Estimating the Trap Efficiency Of Intermittently Dry Reservoirsmentioning
confidence: 99%